Application de la lexigenèse à l’aspect lexical et grammatical - Yves BARDIÈRE (E-REA)
The general framework of this study is that of lexigenesis, a concept devised by G. Guillaume to describe the genesis of words. Lexigenesis, also referred to as ontogenesis, is based on a movement which first particularizes (ideogenesis) and then generalizes (morphogenesis). This paper aims at demonstrating how the lexical aspect and the grammatical aspect can be respectively and successively derived from ideogenesis and morphogenesis.